Using functional shocks to assess conventional and unconventional monetary policy in Canada - Thorsten V. Koeppl; Jeremy M. Kronick; James McNeil (Queen's University, Department of Economics, 2023)
We develop a new series of Canadian monetary policy shocks and analyze their impact on inflation and real GDP from 1996-2020. Our shocks are constructed as the daily change in the Nelson-Siegel yield curve factors after a monetary policy announcement. Because these shocks include information along the entire yield curve, they provide a more comprehensive view of Canadian monetary policy relative to the existing literature, which focuses on shocks to the short-run interest rate. We docu- ment that monetary policy shocks often twist the yield curve, which tends to make monetary policy less effective. Furthermore, we find that lower real interest rates have muted the overall impact of monetary policy over time. Looking at particular episodes, there is little evidence that forward guidance or quantitative easing had a significant impact on inflation or real GDP.
Keywords: E52; E65; C58; G12; 330; Monetary Policy Shocks; Canada; Yield Curve; Local Projections; Unconventional Monetary Policy